A carbon-iron co-doped graphite-phase carbon nitride photo-Fenton catalyst, a preparation method and application thereof
Patent Information
- Application Number
- CN202611199008.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-08
- Publication Date
- 2026-10-27
AI Technical Summary
[0008]针对现有技术中氮化碳基类芬顿催化剂催化活性不足、抗基质干扰能力弱、循环稳定性差,以及制备工艺复杂难以规模化的技术缺陷,本申请提供一种碳铁共掺型石墨相氮化碳光类芬顿催化剂及其制备方法和应用
[0046](1)本申请提供的碳铁共掺型石墨相氮化碳光类芬顿催化剂,通过碳铁的共掺杂构建了多元活性位点,实现了光催化与类芬顿反应的高效耦合。相较于纯石墨相氮化碳,本催化剂带隙能由2.68eV窄化至2.49eV,可见光吸收边带红移近40nm,可见光利用范围显著拓宽;光致发光荧光强度下降超60%,光生电子-空穴对复合被大幅抑制,电荷分离效率显著提升。煅烧过程中,碳原子取代桥接氮原子可在氮化碳主链形成大范围离域π键,显著促进电荷转移;氮空位及掺杂碳物种可作为电子汇进一步截留光生电子,协同Fe-N活性位点形成多维度电荷传输通道,催化本征活性大幅提升,最优体系四环素降解表观速率常数达纯氮化碳体系的3倍以上。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This application relates to the technical field of advanced oxidation water treatment, and in particular to a carbon-iron co-doped graphite phase carbon nitride photocatalyst, its preparation method, and its application. Background Technology
[0002] Urban sewage is a significant pathway for the migration and diffusion of new pollutants in the environment. Every day, a large amount of industrial wastewater and domestic sewage containing new pollutants enters sewage treatment plants through various routes, posing a serious threat to the ecological environment and human health. Traditional sewage treatment processes, focusing on nitrogen and phosphorus removal and suspended solids removal, are insufficient to completely block or deeply remove new pollutants. Advanced oxidation technology, as a deep treatment process, can generate active species to oxidize and decompose recalcitrant organic matter, demonstrating significant technological advantages in the field of new pollutant treatment.
[0003] Heterogeneous photocatalytic Fenton-like catalysis has become a research hotspot and application focus in the field of advanced oxidation due to its synergistic effect of photocatalysis and Fenton oxidation. Photocatalysis itself possesses characteristics such as low energy consumption, easy integration of equipment with existing processes, and environmental friendliness. The activation efficiency of Fenton-like oxidants (such as persulfates and hydrogen peroxide) directly determines the degradation performance of the catalytic system. Carbon-based materials and semiconductor catalysts are currently the two most widely used activation media. Persulfate oxidants mainly include permonosulfates and perdisulfates, both of which can generate active species through activation at transition metal sites and carbon-based defect sites, achieving the oxidative degradation of organic pollutants.
[0004] Graphitic carbon nitride, as a typical non-metallic polymer semiconductor material, has outstanding advantages such as low preparation cost, excellent chemical stability, and visible light response, making it one of the most industrially promising materials in the field of photocatalysis. However, pure-phase carbon nitride has inherent defects such as high recombination rate of photogenerated electron-hole pairs, limited visible light absorption range, and insufficient catalytic activity, making it difficult to directly meet the high-efficiency degradation requirements of advanced wastewater treatment.
[0005] Existing technologies often modify carbon nitride through metal doping, non-metal doping, and morphology control. Iron-doped carbon nitride is a common method for constructing photocatalytic Fenton systems, utilizing Fe sites to activate persulfate and simultaneously combining with the photocatalytic performance of carbon nitride to form a synergistic system. However, single-iron doping systems still have significant shortcomings: firstly, the effect on regulating the electronic structure of carbon nitride is limited, resulting in a limited improvement in photogenerated carrier separation efficiency and making it difficult to fully realize photocatalytic efficiency; secondly, the system mainly uses sulfate radicals and hydroxyl radicals as the main active species, readily reacting with Cl- in water. - HCO3 -Inorganic anions undergo side reactions, are highly susceptible to interference from the environmental matrix, and are difficult to adapt to the complex water quality of urban sewage; thirdly, iron sites are easily dissolved and lost, and the cycle stability of the catalyst needs to be improved, which limits its engineering application.
[0006] The conventional preparation method for graphitic carbon nitride is thermal polymerization, which uses dicyandiamide, melamine, urea and other precursors as precursors and calcines them at a high temperature of 500~600℃ in air atmosphere. Among them, calcination at 550℃ for 2~4h is the most commonly used process conditions in this field. It does not require vacuum or inert atmosphere protection and the process is simple and easy to scale up.
[0007] Therefore, designing and preparing novel functionalized carbon nitride-based high-efficiency and selective catalysts, and developing efficient, low-cost, and easily integrated photo-Fenton coupling technology that can be incorporated into existing processes, are of great practical significance for the effective control of new pollutants in wastewater treatment plants, taking into account the water quality characteristics and process requirements of urban wastewater treatment. Summary of the Invention
[0008] To address the shortcomings of existing carbon nitride-based Fenton catalysts, such as insufficient catalytic activity, weak resistance to matrix interference, poor cycle stability, and complex preparation processes that are difficult to scale up, this application provides a carbon-iron co-doped graphite-phase carbon nitride photocatalyst, its preparation method, and its application.
[0009] Existing single-iron-doped modified carbon nitride has three core bottlenecks: (1) Relying solely on Fe sites to regulate the electronic structure, the reduction in the recombination rate of photogenerated electron-hole pairs is limited, resulting in low photocatalytic energy utilization; (2) The activated oxidant mainly follows the free radical pathway, making it susceptible to quenching by inorganic anions in wastewater, leading to a significant decrease in degradation efficiency in complex water quality; (3) Fe ions are only single-coordinated and anchored, making them prone to dissolution and loss over long-term use, resulting in a short catalyst cycle life. Furthermore, single-carbon doping can only optimize charge separation and cannot efficiently activate persulfate to achieve the Fenton reaction.
[0010] This application employs a one-step thermal polymerization process to achieve simultaneous carbon and iron doping: carbon atoms replace carbon nitride to bridge nitrogen atoms, constructing delocalized π bonds and nitrogen vacancy defects, thus enhancing the separation efficiency of photogenerated carriers; trivalent Fe is firmly anchored to the framework through Fe-N coordination bonds, providing stable Fenton-like active sites; the two work together to construct a multi-path activation mechanism involving ¹O2, photogenerated holes, and high-valent iron species, which not only expands the visible light response range and enhances intrinsic catalytic activity, but also significantly reduces water matrix interference and inhibits iron dissolution. Furthermore, the one-step thermal polymerization process can be used with existing carbon nitride mass production lines, making it easy to scale up and directly embed into existing advanced treatment units in wastewater treatment plants, adapting to the complex water quality requirements of urban wastewater. It efficiently degrades new pollutants in water bodies, possessing advantages such as high catalytic efficiency, good stability, and low cost, and the preparation process is simple and easily scalable.
[0011] In a first aspect, this application provides a carbon-iron co-doped graphite-phase carbon nitride photocatalyst, employing the following technical solution:
[0012] A carbon-iron co-doped graphitic carbon nitride photocatalyst, wherein the carbon-iron co-doped graphitic carbon nitride photocatalyst uses graphitic carbon nitride as a matrix, and carbon and iron elements are co-doped into the matrix through a one-step thermal polymerization method to construct multiple active sites in the matrix, forming a catalytic system that combines photocatalysis and Fenton-like oxidation.
[0013] This application uses graphitic carbon nitride as a matrix and co-dops carbon and iron elements through a one-step thermal polymerization method to construct multiple active sites in the matrix, forming a non-metallic polymer catalyst with synergistic effects of photocatalysis and Fenton oxidation.
[0014] Optionally, the molar amount of iron added is 0.25-1 mmol.
[0015] In one specific embodiment, the molar amount of iron added is 0.25 mmol, 0.5 mmol, 0.75 mmol, or 1 mmol.
[0016] In some specific embodiments, the molar amount of iron added is 0.25-0.5 mmol, 0.25-0.75 mmol, 0.25-1 mmol, 0.5-0.75 mmol, 0.5-1 mmol, or 0.75-1 mmol.
[0017] Optionally, iron is bonded to the carbon nitride framework in a trivalent state via Fe-N coordination bonds; the carbon element replaces the bridging nitrogen atoms in the carbon nitride framework, forming delocalized π bonds and nitrogen vacancy defects in the carbon nitride backbone, which act as an electron sink to promote the separation of photogenerated carriers.
[0018] Optionally, the carbon-iron co-doped graphitic carbon nitride photo-Fenton catalyst is a non-metallic polymer semiconductor catalyst with a visible light absorption sideband of not less than 480 nm and a band gap energy of not more than 2.6 eV.
[0019] The visible light absorption sideband of the carbon-iron co-doped graphitic carbon nitride photocatalyst of this application is not less than 480 nm, and the band gap energy is controlled within 2.6 eV. Through experimental analysis, the absorption sideband of the carbon-iron co-doped graphitic carbon nitride photocatalyst can reach 500 nm, and the band gap energy is as low as 2.49 eV, which greatly improves the visible light capture capability.
[0020] Secondly, this application provides a method for preparing a carbon-iron co-doped graphite phase carbon nitride photocatalyst, employing the following technical solution:
[0021] A method for preparing a carbon-iron co-doped graphitic carbon nitride photocatalyst, the method specifically comprising the following steps:
[0022] (1) Mix dicyandiamide, carbon source and iron source in proportion, and obtain a uniform precursor mixture after mixing treatment. Put the precursor mixture into a covered crucible and seal it.
[0023] (2) The sealed crucible is placed in a calcination device and calcined under a programmed temperature rise in an air atmosphere. After naturally cooling to room temperature, carbon-iron co-doped graphite phase carbon nitride photocatalyst is obtained.
[0024] Optionally, the carbon source is ammonium citrate.
[0025] Optionally, the ammonium citrate is any one or more of triammonium citrate, triammonium citrate, and triammonium citrate.
[0026] Optionally, the iron source is ferric chloride hexahydrate.
[0027] Optionally, the molar ratio of triammonium citrate to dicyandiamide is (0.5~1.5):170.
[0028] Optionally, the mixing process in step (1) is a solid-phase grinding process or a liquid-phase evaporation process.
[0029] Optionally, the solid-phase grinding process is as follows: dicyandiamide, carbon source and iron source are placed in a mortar and mixed and ground for 10 to 60 minutes until the material is uniform.
[0030] Optionally, the liquid phase evaporation process is as follows: dicyandiamide, carbon source and iron source are added to deionized water, magnetically stirred to form a uniform suspension, and continuously stirred in a water bath until the water is completely evaporated to obtain a dry solid mixture.
[0031] Optionally, in step (2), the heating rate of calcination is 2-8℃ / min, the calcination temperature is 500-600℃, and the constant temperature calcination time is 2-4h.
[0032] Optionally, in step (1), the crucible is sealed by tightly wrapping the entire crucible with 3 to 5 layers of aluminum foil with a thickness of 15 to 30 μm.
[0033] Optionally, the forging equipment is a muffle furnace or a box-type atmosphere furnace.
[0034] Thirdly, this application provides the application of a carbon-iron co-doped graphite phase carbon nitride photocatalyst in the degradation of new pollutants in wastewater.
[0035] Optionally, the new pollutants include organic pollutants such as antibiotics, endocrine disruptors, and persistent organic pollutants. Specifically, they include tetracycline, sulfamethoxazole, ofloxacin, and bisphenol A.
[0036] Fourthly, this application provides a method for catalytically degrading new pollutants in wastewater using a carbon-iron co-doped graphitic carbon nitride photocatalyst, employing the following technical solution:
[0037] A method for catalytically degrading new pollutants in wastewater using a carbon-iron co-doped graphite-phase carbon nitride photocatalyst involves dispersing the carbon-iron co-doped graphite-phase carbon nitride photocatalyst into the water body containing the new pollutants, ultrasonically dispersing the catalyst, stirring it in a dark environment until adsorption-desorption equilibrium is reached, adding persulfate oxidant, and carrying out the catalytic degradation reaction under visible light irradiation.
[0038] Optionally, before adding persulfate oxidant, the initial pH of the water to be treated can be adjusted to 5.0~7.0.
[0039] This system has a wide pH range, and can effectively degrade organic pollutants in water with an initial pH of 3 to 9. It is preferable to adjust the initial pH to 5.0 to 7.0, as the catalytic degradation rate is the highest and the interference from inorganic anions is the weakest in this range. It is suitable for the natural neutral water quality of urban sewage and can directly treat conventional municipal secondary sedimentation effluent without additional acid-base adjustment. It is only recommended to fine-tune the pH to 5.0 to 7.0 for strongly acidic (pH < 4) and strongly alkaline (pH > 9) industrial wastewater to ensure stable and high removal efficiency.
[0040] Optionally, the persulfate is a permonosulfate.
[0041] Optionally, the concentration of the carbon-iron co-doped graphite phase carbon nitride photocatalyst is 0.15~0.3g / L, the concentration of persulfate is 0.5~2mM, and the initial concentration of the target new pollutant is 5~20mg / L.
[0042] Optionally, the temperature of the catalytic degradation reaction is 20~30℃, the stirring speed is 500~800rpm, and the reaction time is 10~60min.
[0043] Optionally, the S-Light-AF2 parallel light reactor was used as the reaction generator in the laboratory pilot test; the light source was an adjustable power visible light LED with a wavelength range of 420~780nm; before the instrument was run, circulating cooling water was turned on to cool the LED lamps, and the whole process was carried out under continuous magnetic stirring.
[0044] Optionally, the pilot-scale engineering project uses a visible light-driven baffled corridor reactor as a wastewater treatment plant reactor, which can be directly embedded into the deep treatment unit of existing urban wastewater treatment processes.
[0045] In summary, this application includes at least one of the following beneficial technical effects:
[0046] (1) The carbon-iron co-doped graphitic carbon nitride photocatalyst provided in this application constructs multiple active sites through co-doping of carbon and iron, realizing efficient coupling of photocatalysis and Fenton-like reaction. Compared with pure graphitic carbon nitride, the band gap of this catalyst is narrowed from 2.68 eV to 2.49 eV, the visible light absorption sideband is redshifted by nearly 40 nm, and the visible light utilization range is significantly broadened; the photoluminescence intensity decreases by more than 60%, the recombination of photogenerated electron-hole pairs is greatly suppressed, and the charge separation efficiency is significantly improved. During calcination, carbon atoms can replace bridging nitrogen atoms to form large-scale delocalized π bonds in the carbon nitride backbone, which significantly promotes charge transfer; nitrogen vacancies and doped carbon species can act as electron sinks to further retain photogenerated electrons, and form multi-dimensional charge transport channels in conjunction with Fe-N active sites, greatly improving the intrinsic catalytic activity. The apparent rate constant of tetracycline degradation in the optimal system is more than 3 times that of the pure carbon nitride system.
[0047] (2) The preparation method provided in this application adopts a one-step thermal polymerization method. All dopant sources and carbon nitride precursors are simultaneously polycondensed, without the need for subsequent secondary modification steps. The process is simple, can be completed in an atmospheric air atmosphere, and the conditions are easy to control. It can directly use the existing muffle furnace production line for mass production of carbon nitride, which is suitable for large-scale industrial production. The production process has no high pollution emissions and is environmentally friendly.
[0048] (3) The catalyst of this application is suitable for actual urban sewage scenarios. It can achieve a removal rate of more than 99% for four common antibiotics, namely quinolones, macrolides, sulfonamides and tetracyclines, in the secondary sedimentation tank effluent of multiple sewage treatment plants in China. In the conventional sewage inorganic anion coexistence system, the degradation efficiency decreases by less than 10%, and it has a strong resistance to matrix interference. The matching visible light deflection corridor device can be directly embedded into the existing sewage treatment deep treatment unit without major modification to the original civil engineering and process pipelines, and has excellent engineering compatibility.
[0049] (4) The catalyst Fe in this application is anchored by stable Fe-N coordination bond, and the encapsulation effect of carbon skeleton further inhibits metal dissolution. After four consecutive cycle degradation tests, the degradation rate of the target pollutant remains close to 100% in each cycle, and the catalytic activity is almost unaffected. This is far superior to the less than 70% activity retention rate after cycle of conventional single iron doped catalysts, and has extremely high long-term use stability and recycling performance. Attached Figure Description
[0050] Figure 1This document shows the preparation process of the carbon-iron co-doped graphitic carbon nitride photocatalyst in Example 1 of this application, as well as partial characterization images of Examples 1 and Comparative Examples 2 and 3. Specifically, (a) is a schematic diagram of the preparation process of Example 1-CNCF, (b) is a SEM image of Comparative Example 3-CN, (c) is a SEM image of Comparative Example 2-CNF, (d) and (e) are SEM images of Example 1-CNCF, (f) is an XRD pattern, and (g) is an FTIR pattern.
[0051] Figure 2 The image shows the SEM-EDS elemental distribution of the carbon-iron co-doped graphitic carbon nitride photocatalyst in Example 1 of this application. (a) is the overall spectrum, (b) is the C elemental distribution, (c) is the N elemental distribution, and (d) is the Fe elemental distribution.
[0052] Figure 3 These are TEM images of the catalysts prepared in Example 1 and Comparative Examples 2 and 3 of this application. Among them, (a) is Comparative Example 3-CN, (b) is Comparative Example 2-CNF, and (c) is Example 1-CNCF.
[0053] Figure 4 The images show the XPS, UV-vis DRS, and PL spectra of the catalysts prepared in Example 1 and Comparative Examples 2 and 3 of this application. (a) is the XPS full scan spectrum, (b) is the C 1s spectrum, (c) is the N 1s spectrum, (d) is the Fe 2p spectrum, (e) is the UV-vis DRS spectrum, and (f) is the PL spectrum.
[0054] Figure 5 This image shows the degradation effect of tetracycline on persulfate activated by different catalysts under visible light in Example 5 of this application. (a) and (c) are the degradation curves of tetracycline in different photocatalytic Fenton systems, and (b) and (d) are comparison graphs of the reaction rate constants of different catalytic systems. vis represents visible light conditions.
[0055] Figure 6 This is a diagram showing the effect of using the carbon-iron co-doped graphite phase carbon nitride photocatalyst of Example 1 to degrade different organic pollutants in Example 5 of this application.
[0056] Figure 7 This is a diagram showing the effect of the catalyst in Example 5 of this application on the treatment of organic pollutants in urban sewage. In the diagram, (a) represents the degradation effect, and (b) represents the initial concentration of the main new pollutants in the sewage.
[0057] Figure 8 The graphs show the degradation effect of the catalyst on tetracycline under different influencing factors in Example 6 of this application. (a) represents the effect of iron doping amount, (b) represents the effect of catalyst dosage, and (c) represents the effect of inorganic anions.
[0058] Figure 9 This is a cyclic stability diagram of tetracycline repeatedly treated with the carbon-iron co-doped graphite-phase carbon nitride photocatalyst of Example 1 in Example 7 of this application. Among them, (a) is the degradation curve of each cycle, and (b) is a comparison of the degradation rate of each cycle.
[0059] Figure 10 The figures shown are free radical quenching and electrochemical characterization diagrams from Example 8 of this application. Among them, (a) is the experimental results of free radical scavenging with alcohol quenchers, (b) is the ESR spectrum of ·OH and SO4⁻, (c) is the EIS electrochemical impedance spectroscopy, and (d) is the LSV linear sweep voltammetry curve.
[0060] Figure 11 This is a graph showing the effect of different quenchers on tetracycline degradation in Example 8 of this application. (a) is ascorbic acid (AA), (b) is furfuryl alcohol (FFA), (c) is EDTA-2Na, and (d) is dimethyl sulfoxide (DMSO).
[0061] Figure 12 This is a schematic diagram illustrating the degradation mechanism of tetracycline by the carbon-iron co-doped graphite phase carbon nitride photocatalyst provided in this application.
[0062] Figure 13 This is a degradation pathway diagram of tetracycline degradation by the carbon-iron co-doped graphite phase carbon nitride photocatalyst of this application.
[0063] Figure 14 This is a biotoxicity analysis diagram of the tetracycline degradation products in Example 9 of this application. (a) and (d) represent fish toxicity, (b) and (e) represent daphnia toxicity, and (c) and (f) represent green algae toxicity. Detailed Implementation
[0064] Before describing the embodiments of this application in detail, it should be understood that the terminology used herein is for the purpose of describing a particular embodiment only. Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the term pertains.
[0065] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include one or more of that feature. Furthermore, in the description of this application, unless otherwise stated, "multiple" means two or more.
[0066] The endpoints and any values of the ranges disclosed in this application are not limited to the precise ranges or values, and such ranges or values should be understood to include values close to such ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0067] In this application, the terms "comprising" or "including" are open-ended expressions, meaning they include the content specified in this application but do not exclude other aspects.
[0068] To make the objectives, technical solutions, and advantages of this application clearer, the technical solutions in the embodiments of this application will be clearly and completely described below. All other embodiments obtained by those skilled in the art based on the embodiments of this application without inventive effort are within the scope of protection of this application. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application.
[0069] Where specific techniques or conditions are not specified in the examples, they shall be performed in accordance with the techniques or conditions described in the literature in this field or in accordance with the product instructions. Reagents or instruments whose manufacturers are not specified are all commercially available conventional products.
[0070] The present application will be further described in detail below with reference to the embodiments and test results.
[0071] Example 1
[0072] This embodiment provides a carbon-iron co-doped graphitic carbon nitride photocatalyst. The molar amount of iron added is 0.75 mmol.
[0073] The specific preparation method of this carbon-iron co-doped graphite phase carbon nitride photocatalyst is as follows:
[0074] (1) Weigh 5g of dicyandiamide, 85mg of triammonium citrate and 202.875mg of ferric chloride hexahydrate, put them in a mortar, mix them evenly and grind for 30min.
[0075] (2) Transfer the mixed and ground material to a covered crucible, tightly wrap the crucible with 4 layers of 20μm thick aluminum foil to achieve a seal, put the sealed crucible into a muffle furnace, heat it to 550℃ at a heating rate of 5℃ / min, and calcine at a constant temperature for 2h.
[0076] (3) After the product is naturally cooled to room temperature, it is taken out and ground thoroughly to obtain carbon-iron co-doped graphite phase carbon nitride photocatalyst, denoted as CNCF.
[0077] Example 2
[0078] This embodiment provides a carbon-iron co-doped graphitic carbon nitride photocatalyst. The difference from Example 1 is that the molar amount of iron added is 0.25 mmol, corresponding to a ferric chloride hexahydrate dosage of 67.575 mg, with the ferric chloride hexahydrate dosage adjusted accordingly. All other steps remain the same as in Example 1.
[0079] Example 3
[0080] This embodiment provides a carbon-iron co-doped graphitic carbon nitride photocatalyst. The difference from Example 1 is that the molar amount of iron added is 0.5 mmol, corresponding to a ferric chloride hexahydrate dosage of 135.15 mg, with the ferric chloride hexahydrate dosage adjusted accordingly. All other steps remain the same as in Example 1.
[0081] Example 4
[0082] This embodiment provides a carbon-iron co-doped graphitic carbon nitride photocatalyst. The difference from Example 1 is that the molar amount of iron added is 1 mmol, corresponding to a ferric chloride hexahydrate dosage of 270.30 mg, thus adjusting the ferric chloride hexahydrate dosage accordingly. All other steps remain the same as in Example 1.
[0083] Comparative Example 1
[0084] This comparative example provides a carbon-doped graphitic carbon nitride catalyst. It differs from Example 1 in that ferric chloride hexahydrate is not added; only dicyandiamide and triammonium citrate are added to obtain a carbon-doped graphitic carbon nitride catalyst, denoted as CNC. All other steps are consistent with Example 1.
[0085] Comparative Example 2
[0086] This comparative example provides an iron-doped graphitic carbon nitride catalyst. It differs from Example 1 in that triammonium citrate is not added; instead, dicyandiamide and ferric chloride hexahydrate are added to obtain an iron-doped graphitic carbon nitride catalyst, denoted as CNF. All other steps are consistent with Example 1.
[0087] Comparative Example 3
[0088] This comparative example provides a graphitic carbon nitride catalyst. It differs from Example 1 in that triammonium citrate and ferric chloride hexahydrate are not added; only dicyandiamide is added to obtain a pure graphitic carbon nitride catalyst, denoted as CN. All other steps are consistent with Example 1.
[0089] Performance Test 1
[0090] The catalysts prepared in Example 1 and Comparative Examples 2 and 3 were subjected to the following tests.
[0091] (a) Detection methods
[0092] (1) SEM and SEM-EDS characterization
[0093] The microstructure of the catalyst was observed using field emission scanning electron microscopy with an accelerating voltage of 5-15 kV; elemental distribution was tested using energy-dispersive X-ray spectroscopy, and the sample was uniformly sputtered with gold before testing.
[0094] (2) TEM characterization
[0095] The microstructure and layered morphology of the catalyst were observed using transmission electron microscopy with an accelerating voltage of 200 kV. Before testing, the sample was ultrasonically dispersed in anhydrous ethanol, and the supernatant was dropped onto a copper mesh microgrid and allowed to air dry before testing.
[0096] (3) XRD characterization
[0097] X-ray diffraction was used for crystal phase analysis with a Cu Kα target, wavelength λ=0.15406nm, scanning range 2θ=5°~80°, scanning rate 5° / min, test voltage 40kV, and test current 40mA.
[0098] (4) FTIR characterization
[0099] The functional group structure of the samples was tested using a Fourier transform infrared spectrometer. The samples were prepared using the KBr pellet method. The scanning range was 4000~400cm⁻¹, the resolution was 4cm⁻¹, and the number of scans was 32.
[0100] (5) XPS characterization
[0101] The surface elemental composition and valence state of the samples were analyzed using X-ray photoelectron spectroscopy with an Al Kα ray source and charge correction based on C 1s=284.8eV binding energy.
[0102] (II) Test Results
[0103] Figure 1 This document shows the preparation process of the carbon-iron co-doped graphitic carbon nitride photocatalyst in Example 1 of this application, as well as partial characterization images of Examples 1 and Comparative Examples 2 and 3. Specifically, (a) is a schematic diagram of the preparation process of Example 1-CNCF, (b) is a SEM image of Comparative Example 3-CN, (c) is a SEM image of Comparative Example 2-CNF, (d, e) are SEM images of Example 1-CNCF, (f) is an XRD pattern, and (g) is an FTIR pattern.
[0104] Figure 2The image shows the SEM-EDS elemental distribution of the carbon-iron co-doped graphitic carbon nitride photocatalyst in Example 1 of this application. (a) is the overall spectrum, (b) is the C elemental distribution, (c) is the N elemental distribution, and (d) is the Fe elemental distribution.
[0105] Figure 3 These are TEM images of the catalysts prepared in Example 1 and Comparative Examples 2 and 3 of this application. Among them, (a) is Comparative Example 3-CN, (b) is Comparative Example 2-CNF, and (c) is Example 1-CNCF.
[0106] Figure 4 The images show the XPS, UV-vis DRS, and PL spectra of the catalysts prepared in Example 1 and Comparative Examples 2 and 3 of this application. (a) is the XPS full scan spectrum, (b) is the C 1s spectrum, (c) is the N 1s spectrum, (d) is the Fe 2p spectrum, (e) is the UV-vis DRS spectrum, and (f) is the PL spectrum.
[0107] The results are analyzed as follows:
[0108] Depend on Figure 1 SEM images (b), (c), (d), and (e) show that all catalysts consist of irregular crystallites and exhibit some agglomeration. Figure 2 The SEM-EDS elemental spectra showed that carbon and iron elements were uniformly distributed and well dispersed in the carbon-iron co-doped graphitic carbon nitride photocatalyst of Example 1. Figure 3 TEM images show that all catalysts exhibit typical layered and lamellar structures of carbon nitride. The interlayer spacing of CNCF is slightly larger than that of pure CN, confirming that doping promotes interlayer exfoliation.
[0109] Depend on Figure 1 The (f) XRD patterns show that all catalysts exhibit typical carbon nitride crystalline phases. The characteristic peak at 27.4° corresponds to the interlayer stacking of conjugated aromatic rings (002 crystal plane), while the weak peak at 13.1° corresponds to the in-plane structure of triazine units (100 crystal plane). The diffraction peak positions of CNCF are consistent with CN, indicating that the basic crystal structure of carbon nitride has not changed; however, the peak intensity is significantly reduced and the diffraction angle is slightly shifted upward, indicating that carbon-iron co-doping inhibits grain growth and introduces lattice defects. Furthermore, no characteristic peaks of iron oxides were detected, indicating that Fe is mainly bonded to the carbon nitride framework through Fe-N bonds.
[0110] Depend on Figure 1 The (g) FTIR spectra show that the characteristic vibrational modes of CN and CNCF are basically the same, indicating that the modification did not destroy the basic structure of carbon nitride. (3075~3250 cm⁻¹) -1 The broad peak at 1010~1750 cm⁻¹ corresponds to the NH stretching vibration. -1The absorption band at 808 cm⁻¹ corresponds to the stretching vibration of the CN heterocycle. -1 The sharp peak at this point is a characteristic bending vibration of the triazine ring. Compared to CN, CNCF exhibits a higher peak at 3000–3100 cm⁻¹. -1 The NH peak intensity decreased, while the peak intensity of the aromatic CN heterocycle increased, indicating that carbon doping promoted the condensation reaction of carbon nitride, forming more cyano structures.
[0111] Depend on Figure 4 XPS plots (a), (b), (c), and (d) show that the C 1s spectrum of CNCF has characteristic peaks at 284.8 eV (surface adsorbed carbon) and 288.4 eV (sp²C in NC=N), while the N 1s spectrum has characteristic peaks at 398.8 eV (aromatic nitrogen in CN=C) and 400.2 eV (tertiary nitrogen in C-NH-C). Compared to CN, the C 1 peak intensity of CNCF increases while the C 2 peak intensity decreases, indicating that the carbon produced by the decomposition of triammonium citrate replaces the bridging nitrogen in the carbon nitride framework; the slight downward shift in the binding energy of the N 2 peak further confirms this conclusion. The characteristic peaks at 711.1 eV and 724.7 eV in the Fe 2p spectrum correspond to Fe 2p 3 / 2 and Fe 2p 1 / 2 The orbitals indicate that Fe exists in the form of Fe(III) and coordinates with N atoms to form Fe-N bonds, consistent with the XRD results.
[0112] Depend on Figure 4 The (e)UV-Vis DRS plot shows that the absorption sideband of CNCF redshifts from 460 nm in CN to 500 nm, and the band gap narrows from 2.68 eV to 2.49 eV, indicating that its visible light absorption range has been effectively extended. Figure 4 As can be seen from the (f)PL spectrum, CN has a strong fluorescence emission peak at 463 nm, while the fluorescence intensity of CNCF is significantly reduced, indicating that carbon-iron co-doping effectively suppresses the recombination of photogenerated electron-hole pairs.
[0113] Example 5
[0114] The carbon-iron co-doped catalyst-activated PMS system in this application relies on a non-radical oxidation pathway, which differs from the traditional homogeneous Fenton system and can achieve pollutant degradation within a wide pH range of 3-9. To unify experimental variables and obtain optimal kinetic performance, the initial pH of the water body in this embodiment is uniformly controlled to be stable at 6.0±0.2. For urban domestic sewage with a natural pH of 5.0-7.0, no additional acid or alkali adjustment is required, and this method can be used directly to achieve efficient removal of new pollutants. Only for strongly acidic and strongly alkaline industrial wastewater, it is recommended to fine-tune the pH to 5.0-7.0 to eliminate the inhibitory effect of extreme pH on the generation of high-valence iron and singlet oxygen.
[0115] This example investigated the degradation effects of different catalysts on tetracycline by activated persulfate (Oxone, 2KHSO5 KHSO4 ⋅ K2SO4, abbreviated as PMS) under visible light, as well as the synergistic performance of different reaction modes. The catalysts investigated were those prepared in Example 1 and Comparative Examples 1-3.
[0116] The specific method is as follows:
[0117] (1) Take 10 mg of catalyst and add it to 50 mL of tetracycline solution with an initial concentration of 10 mg / L. The catalyst dosage is 0.2 g / L. Use dilute hydrochloric acid / sodium hydroxide to adjust the initial pH of the water body to be stable at 6.0 ± 0.2.
[0118] (2) After ultrasonically dispersing the mixture for 30 seconds, stir it at 600 rpm for 20 minutes in the dark to establish an adsorption-desorption equilibrium.
[0119] (3) Add 1mM PMS and turn on the visible light LED light source in the S-Light-AF2 parallel light reactor. Perform photo-Fenton reaction under continuous magnetic stirring and 25°C conditions.
[0120] (4) Take samples at regular intervals and add 1 mL of 100 mM Na2S2O3 solution to terminate the reaction. After filtration through a 0.22 μm PTFE filter membrane, determine the tetracycline concentration by high performance liquid chromatography (detection wavelength 357 nm, mobile phase is acetonitrile: 0.1% formic acid water = 20:80).
[0121] The degradation effects of different catalysts on tetracycline by persulfate (PMS) activated under visible light are as follows: Figure 5 As shown.
[0122] Depend on Figure 5 (a) and (b) show that the blank group (PMS + visible light only) had almost no degradation effect on tetracycline. The order of photo-Fenton activity of the four catalysts was CNCF > CNC ≈ CNF > CN. Among them, the CNCF system with carbon and iron co-doping showed the best performance, with an apparent pseudo-first-order reaction rate constant of 0.075 min⁻¹. The removal rate of tetracycline reached more than 95% after 30 min of reaction and complete degradation was achieved within 60 min. This was significantly better than the single-doped and pure carbon nitride systems, which confirmed that carbon and iron co-doping produced a significant synergistic effect.
[0123] Further comparison of the degradation performance of pure CN and CNCF under three modes—photocatalysis alone, dark-state Fenton-like mode, and light-state Fenton-like mode—results are as follows: Figure 5As shown in (c) and (d), both catalysts exhibited the best activity in the photo-Fenton-like system. The photo-Fenton-like rate constant of CNCF was 4.2 times that of its photocatalytic system alone and 3.3 times that of the dark-state Fenton-like system, indicating a significant synergistic effect between photocatalysis and Fenton-like oxidation, which can jointly promote the degradation of pollutants.
[0124] The degradation effect of the carbon-iron co-doped graphitic carbon nitride photocatalyst of Example 1 on different organic pollutants was further investigated, and the test results are as follows: Figure 6 As shown.
[0125] Depend on Figure 6 It is known that the carbon-iron co-doped graphite phase carbon nitride photoluminescent Fenton catalyst provided in this application has a good degradation effect on a variety of organic pollutants such as sulfamethoxazole (SMX), ofloxacin (OFL), bisphenol A (BPA), and tetracycline (TC).
[0126] Furthermore, using the effluent from the secondary sedimentation tank of a wastewater treatment plant in a town in Central China as the treatment object, the degradation effect of the carbon-iron co-doped graphite-phase carbon nitride photocatalyst of Example 1 on actual wastewater was tested. The test results are as follows: Figure 7 As shown.
[0127] Depend on Figure 7 It is known that the carbon-iron co-doped graphite phase carbon nitride photocatalyst provided in this application has a removal rate of over 99% for quinolone antibiotics and macrolide antibiotics in actual wastewater, which can effectively cope with the complex matrix interference of actual wastewater and achieve efficient removal of conventional emerging pollutants.
[0128] Example 6
[0129] This embodiment investigated the effects of different influencing factors on the degradation of tetracycline by persulfate activated by the catalyst under visible light. All experiments maintained the initial pH of the water at 6.0±0.2.
[0130] (1) Investigation of iron doping amount: The carbon-iron co-doped graphitic carbon nitride photocatalysts provided in Examples 1-4 were investigated. Under the method provided in Example 5, the effect of different iron doping amounts on the degradation effect of tetracycline was investigated.
[0131] (2) Catalyst dosage was investigated: The catalyst dosage was 7.5 mg, 10 mg, 12.5 mg, and 15 mg (corresponding to concentrations of 0.15 g / L, 0.2 g / L, 0.25 g / L, and 0.3 g / L), based on the carbon-iron co-doped graphitic carbon nitride photocatalyst provided in Example 1. The effect of catalyst dosage on tetracycline degradation was investigated using the method provided in Example 5.
[0132] (3) Investigating inorganic anions: The object of investigation is Cl. -SO4 2- H2PO4 - HCO3 - Following the method provided in Example 5, 5 mM inorganic anions were added before establishing adsorption-desorption equilibrium to investigate the effect of inorganic anions on the degradation of tetracycline.
[0133] Test results as follows Figure 8 As shown.
[0134] Depend on Figure 8 (a) It can be seen that there is an optimal doping amount for iron loading. The catalytic activity is optimal when the molar amount of iron added is 0.75 mmol. When the doping amount is too low, there are insufficient active sites, and when it is too high, charge recombination is easily triggered, resulting in a decrease in activity.
[0135] Depend on Figure 8 (b) It can be seen that as the amount of catalyst added increases, the catalytic activity of the system gradually improves, but there is a certain threshold. When the amount added is too high, the efficiency improvement will slow down due to the light shading effect.
[0136] Depend on Figure 8 (c) It can be seen that Cl - and SO4 2- It has no significant effect on tetracycline degradation, H2PO4 - and HCO3 - It has a certain inhibitory effect on the degradation process, and H2PO4 - The degree of inhibition is higher than that of HCO3 - Overall, the system exhibits strong tolerance to common inorganic anions and is suitable for treating complex water conditions.
[0137] Example 7
[0138] This embodiment examines the cycle stability of the carbon-iron co-doped graphitic carbon nitride photocatalyst of Example 1. The specific method is as follows:
[0139] (1) Take 10 mg of the carbon-iron co-doped graphite phase carbon nitride photo-Fenton catalyst from Example 1 and add it to 50 mL of tetracycline solution with an initial concentration of 10 mg / L. Adjust the initial pH to 6.0 ± 0.2, disperse ultrasonically for 30 s, and then stir at 600 rpm for 20 min in the dark to establish adsorption-desorption equilibrium. Add 1 mM PMS and react under visible light for 30 min.
[0140] (2) After the reaction was completed, the catalyst was recovered by centrifugation, washed three times with deionized water and anhydrous ethanol, and dried overnight in an oven at 80°C. The recovered catalyst was reused in the tetracycline degradation experiment under the same conditions for a total of four cycles.
[0141] Test results as follows Figure 9 As shown.
[0142] Depend on Figure 9 It can be seen that after four consecutive cycles, the degradation rate of tetracycline in each cycle is close to 100%, and the catalytic activity does not decrease significantly. This indicates that the carbon-iron co-doped graphitic carbon nitride photocatalyst prepared in this application has excellent structural stability and recycling performance, which is far superior to the significant decrease in activity after cycling of conventional single iron-doped carbon nitride catalysts.
[0143] Example 8
[0144] This embodiment examines the reaction mechanism of the carbon-iron co-doped graphite phase carbon nitride photocatalyst for the catalytic degradation of tetracycline in water by the Fenton catalyst of Example 1.
[0145] The reaction mechanism was investigated using quenching experiments, electrochemical characterization, and ESR characterization. The specific methods are as follows:
[0146] (1) Ethanol, methanol, and tert-butanol at different concentrations (0-100 mM) were added to the reaction system as free radical quenchers, as well as furfuryl alcohol (¹O2 quencher) at 0-10 mM and EDTA-2Na (h2O2 quencher) at 0-1.0 mM. + Quenching agent), 0-2.0 mM ascorbic acid (·O2) - The effects of quenching agent and 0-200 mM dimethyl sulfoxide (high-valent iron probe reagent) on the degradation rate of tetracycline were investigated.
[0147] (2) The electrochemical impedance spectroscopy (EIS) and linear sweep voltammetry (LSV) curves of different catalyst systems were tested using a CHI 760E electrochemical workstation.
[0148] (3) The active species in the system were detected by ESR characterization, with DMPO as ·OH and SO4·⁻ scavenger and TEMP as ¹O2 scavenger.
[0149] Test results as follows Figure 10 , Figure 11 As shown.
[0150] Depend on Figure 10 (a) It can be seen that after adding hydroxyl radical and sulfate radical quenchers such as ethanol, methanol, and tert-butanol, the tetracycline degradation efficiency only decreased slightly, indicating that ·OH and SO4·⁻ are not the main active species of the system. Figure 10 The ESR results in (b) also showed that only a weak DMPO-radical adduct signal was detected in the system, further confirming that the radical pathway contributed a limited amount.
[0151] Depend on Figure 11It was found that the addition of furfuryl alcohol (¹O2 quencher) and EDTA-2Na (h⁺ quencher) significantly reduced the tetracycline removal rate, and the inhibitory effect increased with increasing quencher concentration, indicating that ¹O2 and photogenerated holes play a key role in the degradation process. The addition of ascorbic acid had no significant effect on degradation, indicating that ·O2⁻ contributed little. The addition of dimethyl sulfoxide significantly reduced the tetracycline degradation rate, and the characteristic product of dimethyl sulfoxide oxidation to dimethyl sulfone could be detected, confirming the presence of high-valence iron species such as Fe(V)=O in the system and their participation in the degradation process.
[0152] Depend on Figure 10 (c) The electrochemical impedance spectroscopy shows that, compared with pure CN, the CNCF system has a smaller impedance arc radius, lower charge transfer resistance, and better conductivity, which is beneficial for interfacial electron transfer; Figure 10 The linear sweep voltammetry curves in (d) show that the current density increases after the addition of PMS, and further increases significantly after the addition of tetracycline, indicating that CNCF and PMS can form a surface-reactive complex. The electron contribution of tetracycline can promote the activation of PMS and accelerate the degradation reaction. The oxidative activation of PMS at electron-deficient carbon sites is an important pathway for CNCF to activate PMS. Combined with the nitrogen vacancy-mediated energy transfer process, ¹O2 ultimately becomes the dominant reactive oxygen species in the system, exhibiting selective degradation ability for organic pollutants containing electron-donating groups, while effectively avoiding the quenching interference of inorganic anions.
[0153] Based on the above results, the catalytic mechanism of this system is as follows: Figure 12 As shown.
[0154] Depend on Figure 12 As shown, under visible light irradiation, valence band electrons in CNCF transition to the conduction band, generating photogenerated electron-hole pairs. The delocalized π bonds formed by carbon atoms replacing bridging nitrogen broaden the electron transport channels. Nitrogen vacancies and doped carbon species act as electron sinks, rapidly capturing photogenerated electrons and significantly suppressing carrier recombination. Conduction band electrons reduce adsorbed O2 to ·O2⁻, while PMS can capture electrons to generate a small amount of SO4·⁻. SO4·⁻, ·OH, and ·O2⁻ further react to generate ¹O2. On the other hand, PMS adsorbs on the CNCF surface to form reactive complexes, generating ¹O2 through energy transfer pathways. At the same time, Fe-N sites interact with PMS to generate high-valence iron species such as Fe(V)=O. Ultimately, the efficient and highly selective degradation of pollutants is achieved by the combined action of ¹O2, photogenerated holes, and high-valence iron species.
[0155] The degradation pathway of tetracycline is as follows: Figure 13 As shown, there are four main degradation pathways, all of which eventually undergo gradual ring-opening and cleavage into smaller molecule compounds, and are further completely mineralized into H2O and CO2:
[0156] Pathway I: Tetracycline (m / z=445) first undergoes dehydroxylation, removal of amide groups, and double bond reduction to generate an intermediate (m / z=372); subsequently, polycyclic ring opening, demethylation, and dehydroxylation reactions occur to generate an intermediate with a lower molecular weight (m / z=275); after further ring opening of the benzene ring and removal of oxygen-containing functional groups, a small molecule intermediate (m / z=196) is obtained, which finally enters the mineralization stage.
[0157] Pathway II: The C=C bond on the tetracycline molecule undergoes a hydroxylation addition reaction to generate a hydroxylated intermediate (m / z=461); subsequently, through demethylation, dehydroxylation, amino conversion, and partial ring-opening reactions, an intermediate is obtained (m / z=388); further polycyclic ring-opening, oxidation, and functional group removal occur to generate an oxygen-containing intermediate (m / z=309), which is finally cleaved into a small molecule and mineralized.
[0158] Pathway III: Tetracycline undergoes a methyl group removal from its dimethylamino group, transforming it into a methylamino group, yielding a monomethylated intermediate (m / z=431); subsequently, through ring-opening, deamidation, and dehydroxylation reactions, an intermediate is generated (m / z=345); further through bond breaking, functional group rearrangement, and degradation, an intermediate is obtained (m / z=272), which is eventually mineralized step by step.
[0159] Pathway IV: The dimethylamino group of tetracycline is completely demethylated to a primary amino group, yielding a dimethylated intermediate (m / z=417); subsequently, polycyclic ring opening, deamidation, and multi-step bond breaking reactions occur to generate an intermediate (m / z=262); further deamination and hydroxylation reduction yield an intermediate (m / z=238), which finally enters the mineralization stage.
[0160] The intermediate products generated by the above four pathways are eventually broken down into small molecule organic acids, ketones and alcohols with m / z=116, m / z=114 and m / z=104, and are eventually completely oxidized to H2O and CO2.
[0161] Example 9
[0162] This embodiment examines the biotoxicity risk of the carbon-iron co-doped graphitic carbon nitride photocatalyst used in Example 1 for the catalytic degradation of tetracycline in water. The specific method is as follows:
[0163] The biotoxicity of tetracycline degradation intermediates was assessed using the ECOSAR 2.2 procedure. Assessment indicators included acute and chronic toxicity to fish, daphnia, and green algae. Results are as follows: Figure 14 As shown.
[0164] Depend on Figure 14It is evident that the total ecotoxicity of the tetracycline degradation intermediates is significantly lower than that of the original pollutant. The acute toxicity parameters of most intermediates exceed the safety threshold of 100 mg / L, and the chronic toxicity also decreases simultaneously. This indicates that this application can significantly reduce the ecological risk of tetracycline while efficiently degrading it, demonstrating good environmental safety.
[0165] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of this application. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples.
[0166] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of this application.
Claims
1. A carbon-iron co-doped graphitic carbon nitride photocatalyst, characterized in that, The carbon-iron co-doped graphitic carbon nitride photocatalyst uses graphitic carbon nitride as a matrix. Carbon and iron elements are co-doped into the matrix through a one-step thermal polymerization method to construct multiple active sites in the matrix, forming a catalytic system that combines photocatalysis and Fenton-like oxidation.
2. The carbon-iron co-doped graphitic carbon nitride photocatalyst according to claim 1, characterized in that, The molar amount of iron added is 0.25-1 mmol.
3. The carbon-iron co-doped graphitic carbon nitride photocatalyst according to claim 1, characterized in that, Iron is bonded to the carbon nitride framework in a trivalent state via Fe-N coordination bonds; the carbon element replaces the bridging nitrogen atoms in the carbon nitride framework, forming delocalized π bonds and nitrogen vacancy defects in the carbon nitride backbone.
4. The carbon-iron co-doped graphitic carbon nitride photocatalyst according to claim 1, characterized in that, The carbon-iron co-doped graphitic carbon nitride photocatalyst is a non-metallic polymer semiconductor catalyst with a visible light absorption sideband of not less than 480 nm and a band gap energy of not more than 2.6 eV.
5. A method for preparing a carbon-iron co-doped graphitic carbon nitride photocatalyst according to any one of claims 1-4, characterized in that, The preparation method specifically includes the following steps: (1) Mix dicyandiamide, carbon source and iron source in proportion, and obtain a uniform precursor mixture after mixing treatment. Put the precursor mixture into a covered crucible and seal it. (2) The sealed crucible is placed in a calcination device and calcined under a programmed temperature rise in an air atmosphere. After naturally cooling to room temperature, carbon-iron co-doped graphite phase carbon nitride photocatalyst is obtained.
6. The preparation method according to claim 5, characterized in that, The carbon source is ammonium citrate; Optionally, the ammonium citrate is any one or more of triammonium citrate, triammonium citrate, and triammonium citrate. Optionally, the iron source is ferric chloride hexahydrate; Optionally, the molar ratio of triammonium citrate to dicyandiamide is (0.5~1.5):
170.
7. The preparation method according to claim 5, characterized in that, The mixing process described in step (1) is either solid-phase grinding or liquid-phase evaporation. Optionally, the solid-phase grinding process is as follows: dicyandiamide, carbon source and iron source are placed in a mortar and mixed and ground for 10 to 60 minutes until the material is uniform; Optionally, the liquid phase evaporation process is as follows: dicyandiamide, carbon source and iron source are added to deionized water, magnetically stirred to form a uniform suspension, and continuously stirred in a water bath until the water is completely evaporated to obtain a dry solid mixture.
8. The preparation method according to claim 5, characterized in that, In step (2), the heating rate of calcination is 2-8℃ / min, the calcination temperature is 500-600℃, and the constant temperature calcination time is 2-4h. Optionally, the crucible described in step (1) is sealed by tightly wrapping the crucible with 3 to 5 layers of aluminum foil with a thickness of 15 to 30 μm. Optionally, the calcination equipment is a muffle furnace or a box-type atmosphere furnace.
9. The application of the carbon-iron co-doped graphite-phase carbon nitride photocatalyst according to any one of claims 1-4 in the degradation of new pollutants in wastewater; Optionally, the new pollutants include antibiotics, endocrine disruptors, and persistent organic pollutants.
10. A method for catalytically degrading new pollutants in wastewater using a carbon-iron co-doped graphitic carbon nitride photocatalyst as described in any one of claims 1-4, characterized in that, The method includes the following steps: The carbon-iron co-doped graphitic carbon nitride photocatalyst was dispersed in the water body containing new pollutants. After ultrasonic dispersion, it was stirred in the dark until adsorption-desorption equilibrium was reached. Persulfate oxidant was added, and catalytic degradation reaction was carried out under visible light irradiation. Optionally, before adding persulfate oxidant, the initial pH of the water to be treated is adjusted to 5.0~7.0; Optionally, the persulfate is a permonosulfate; Optionally, the concentration of the carbon-iron co-doped graphitic carbon nitride photocatalyst is 0.15~0.3 g / L, the concentration of persulfate is 0.5~2 mM, and the initial concentration of the target new pollutant is 5~20 mg / L; Optionally, the temperature of the catalytic degradation reaction is 20~30℃, the stirring speed is 500~800rpm, and the reaction time is 10~60min.
